The mediating role of intention of learning behaviour in learning behaviour - Li, Xianhui; Wang, Zhanjun; Xie, Jingyu (Frontiers in Psychology, 2024)
Improving the quality of postgraduate study is one that must be addressed with the increase in the number of postgraduate students. This study aims to analyse the effects of learning attitude, learning motivation and self-efficacy on learning behaviour through the intention of learning behaviour, and the effect of learning behaviour on learning outcome. Measurements were made on 560 postgraduate students after the development of a scale. The scale was analysed for reliability and exploratory factor analysis using SPSS software. The date were then analysed using structural equation modelling (SEM) analysis techniques with path analysis and bootstrap methods. The results of the study showed that students’ attitudes towards learning and self-efficacy had a significant indirect on learning behaviour through the mediating involvement of intention to learn behaviours, and learning behaviour had a significant effect on learning outcome. Therefore, there is a need to improve learning behaviour by improving students’ intention to learn behaviour so that they can have good learning outcome.